How might changes to family income affect the likelihood of children being in out-of-home care? Evidence from a realist and qualitative rapid evidence assessment of interventions. (December 2022) - Wood, S.; Scourfield, J.; Stabler, L.; Addis, S.; Wilkins, D.; Forrester, D.; Brand, S.L.
Highlights: Realist EMMIE framework provides actionable findings for policy makers. How interventions that change family income work, for whom and under what circumstances. Increasing family income may help to reduce the rate of children in care. Role for social workers to provide budgets for families as a preventative measure. Abstract: Interventions that change family income include any policy or practice that directly or indirectly changes the amount of money a family have. Although theory regarding the relationship between poverty and child maltreatment is well established, theories of how family income change affects the likelihood of children being in out-of-home are not well developed. This realist rapid evidence assessment provides an overview of the process of how interventions that change family income affect the rate of children in out-of-home care. The study population is families at risk of their children entering care and families whose children are in care and are pursuing reunification. Ten studies were identified from an earlier scoping review. Intervention effect results are described and qualitative evidence about mechanisms and moderators is presented as an initial "programme theory". The review makes an initial suggestion of four pathways through which a change in family income can alter the risk of child abuse and neglect and thus affect the rate of children in out-of-home care. These are: 1) the impact of employment; 2) changes to the home environment; 3) risk/prevention of homelessness; 4) building trusting relationships with social workers. National or local policies which increase a family's income, for instance through tax and benefits regimes or the provision of free childcare, could potentially reduce the rate of children in out-of-home care. There is also a role for social workers in providing direct material help to families. More work is needed to develop intervention theories and better understanding of the process of using material resources to help families at risk of their children being in out-of-home care.